Wacana Poros Partai Islam untuk PILPRES 2024: Politik Identitas atau Penggalangan Suara Oposisi? (State Islamic Institute of Kudus (IAIN Kudus), 2021)
Amidst increasing polarization of society after the 2014 and 2019 presidential elections, identity politics has been reintroduced by Islamic political parties. PKS and PPP are trying to initiate the Islamic pollitical axis for 2024 elections. The discourse about Islamic political axis springs due to the fact that incumbents cannot re-nominate as president for next election. Secondly, public trust level toward the executive has decreased due to various unpopular policies that brought about increasing critical voices toward the government. From the internal ummah, the presence of Islamic political figures who consitently won various surveys, stimulates the passion of Islamic political parties to form coalitions to win 2024 presidential election. This study uses a qualitative approach with content analysis methods toward various sources of literature; book, ebook, scientific journals, articles on conference proceedings, as well as journalistic works on the Islamic political axis discourse from identity politics theory, and theories of party coalition’s perspective that introduced by Lijphart and Rikers. The phenomenon of the coalition of Islamic political parties – once called the center axis – has succeeded in bringing KH Abdurrahman Wahid as President, defeating the candidate of the party that won the 1999 election. The similarity of identity (ideological) and interests (pragmatic) became the basis of the coalition of Islamic political parties. In addition to these two reasons, the discourse of the Islamic axis coalition in the 2024 election is also motivated by dissatisfaction with the performance and policies of the incumbent government. The regulation of the Presidential Threshold for presidential candidacy as stated by law number 7 year 2017 makes the coalition of Islamic political parties can be function as an alternative house in accomodating opposition voices. However, the elite of Islamic political parties is divided in responding to the discourse of the Islamic political axis. PKS, PPP, PKB. PBB, and Masyumi (Reborn) supports the idea of a coalition based on political calculations and the interests of each political party. On the other hand, PAN and the Gelora Party reject the discourse which is worried to be increasing polarization in Indonesian society. The Ummat Party's skepticism is backed by the view that the existing parliamentary Islamic political parties are not serious to grasp the aspirations of the ummah and have not been able to offer alternative policies for a better Indonesia.